Absorption edge of nanocrystalline cubic silicon carbide films - Lopin, A.V.; Semenov, A.V.; Puzikov, V.M.; Skorik, S.N. (Functional Materials, 2009)
The optical absorption edge of nanocrystalline films of cubic silicon carbide polytype (nc-SlC) obtained by direct ion deposition have been studied using optical spectroscopy. Within the 1.12-6.5 eV, three optical absorption regions have been found with different (exponential, power, and oscillating) dependences of the film absorption coefficient on the photon energy. Basing on the proposed structure model, the spectral dependence of absorption coefficient has been related to the defect states of nc-SlC, to direct and indirect optical interband transitions, and with dimensional quantization effects.